1998
DOI: 10.1046/j.1523-1747.1998.00264.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipogenesis in the Human Sebaceous Gland: Glycogen and Glycerophosphate are Substrates for the Synthesis of Sebum Lipids

Abstract: The lipid class compositions of freshly isolated and overnight maintained human sebaceous glands were determined using high performance thin layer chromatography and were found to be broadly similar. The lipid classes identified in freshly isolated glands were broadly similar to those generated from various radiolabeled precursors in vitro, although lower amounts of wax/sterol esters and cholesterol were observed in vitro. We determined the glycogen content of sebaceous glands and showed that during their incu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 23 publications
4
56
0
1
Order By: Relevance
“…For the purposes of this analysis, we chose to use the independent observer’s assessment of hair loss because independent observers have been shown to be more objective at rating hair loss than subjects [19]. The degree of hair loss was classified into two categories of ‘no hair loss’ and ‘hair loss’.…”
Section: Methodsmentioning
confidence: 99%
“…For the purposes of this analysis, we chose to use the independent observer’s assessment of hair loss because independent observers have been shown to be more objective at rating hair loss than subjects [19]. The degree of hair loss was classified into two categories of ‘no hair loss’ and ‘hair loss’.…”
Section: Methodsmentioning
confidence: 99%
“…Experiments based on the incorporation of radiolabeled acetate, have demonstrated that the SG possesses the capacity to synthesize lipids de novo (Summerly and Woodbury 1971;Guy et al 1999). Based on the patterns of lipids synthesized from different exogenous substrates, it has been suggested that NADPH was a limiting and directing factor of the sebaceous lipids biosynthesis in isolated SG (Middleton et al 1988;Downie and Kealey 1998). Exogenous radiolabeled glucose, a good source of NADPH, favors TG synthesis, whereas exogenous radiolabeled acetate, a poor source of NADPH, is in favor of squalene.…”
Section: Squalene Chemistry and Biosynthetic Pathwaysmentioning
confidence: 99%
“…Following glycogen breakdown, glycerophosphate is as important as NADPH in governing the sebaceous lipogenesis. Squalene synthesis is favored over TG when acetate and glutamine are the substrates, independently on the glycogen status of the gland (Downie and Kealey 1998).…”
Section: Squalene Chemistry and Biosynthetic Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Sabe-se que o colesterol é obtido a partir do esqualeno (Downie;Kealey, 1998;Pappas et al, 2009). O esqualeno, juntamente com os ésteres de cera, têm origem na glândula sebácea; os TG originam-se tanto nas glândulas sebáceas quanto na epiderme; os AGL são obtidos pela lipólise bacteriana dos TG ou por esterases presentes no ducto sebáceo; por fim, o colesterol e seus ésteres têm origem epidérmica, predominantemente (Cotterill et al, 1972 Quanto maior o tamanho das GS, maior a participação lipídica do esqualeno na secreção do SB.…”
Section: Ou III Em Uso Sistêmico De Limeciclina E/ou Suplementaçãunclassified